PANDANGAN TOKOH AGAMA TENTANG KHITBAH WANITA KEPADA LAKI-LAKI (Studi Kasus Desa Tenggulun Kecamatan Solokuro Kabupaten Lamongan) - Arisa Sifa; Masrokhin Masrokhin (JOURNAL SAINS STUDENT RESEARCH, 2025)
The engagement begins with the woman's family asking the man's family, either directly or through an intermediary. If the man agrees, the process will continue with a series of processions, one of which is the official engagement, where the woman's family visits the man's family with the extended family. This study aims to examine the process involved when a woman proposes to a man and to gain a clearer understanding of the Islamic legal perspective on women proposing to men in Tenggulun Village. This research is based on direct observation and employs an Islamic law approach with an empirical nature. Data sources consist of primary and secondary data. Data collection techniques include interviews, while data analysis is conducted through interviews, observations, field notes, and document review.The tradition of women proposing to men is a practice that has been continuously carried out and passed down from previous ancestors. The process consists of three stages: first, naren. second, gemblongan and third, determining the wedding date. This study analyzes the phenomenon based on fiqh principles, which recognize urf as a source of law as long as it does not contradict Islamic teachings. Based on the findings, this research indicates that the tradition of women proposing in Tenggulun Village falls under urf shahih, meaning it is a valid and acceptable custom in Islam as it meets the requirements of sharia. This study emphasizes that Islam can accommodate local traditions as long as they adhere to Islamic principles.